MORTALITAS HAMA WERENG PUNGGUNG PUTIH SETELAH DIMANGSA OLEH SERANGGA PREDATOR (PENGAMATAN VISUALISASI DI GREEN HOUSE) - Sjakoer, Nour Athiroh Abdoes (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2010)
The usage of pesticide to eradicate pest cause resurgence, resistance, explosion of secondary pest and the destroyed of the natural enemy. One of pest that attack paddy is white back pest (Sogatella furcifera Horvath). By using the natural enemy of predatory insect able to decrease the pesticide usage. The research aimed at knowing the predation of Synharmonia conglobata Linnaeus predator toward white back pest (Sogatella furcifera Horvath) as the prey and the influence of dark and light time. The research is experimental research by using random design with two treatments and 4 replications. The treatment with predator given symbol (P) used 2 predators and 25 pests. And the without predators given symbol as (K). The data collection was done in 14 days, at 07.00 WIB and 15.00 WIB with 2 days interval. The research parameter is the preyed pest by predator. Data analysis by using unpaired t test with significance level of 1% The results showed that Synharmonia conglobata Linnaeus has predation toward white back pest (Sogatella furcifera Horvath). From data, the predator prey pest in the light time 1.18 pest per day and in dark time 0.94 pest per day. Based on t test (0.01) showed the significant differences between treatment and control wither in light or dark time.Keywords: Mortality, predatory insect, white back pest, and visualisation.